All you need is coffe - Fabiani, Camila (2017)
Cholinergic deficit is regarded as an important factor responsible for Alzheimer’s disease symptoms. Two molecular targets for the treatment of this disease are acetylcholinesterase (AChE) and nic otinic receptor (nAChR). Caffeine (CAFF) acts as a non-competitive inhibitor of AChE but its mechanism of action on nAChR is still un known. To this end, we first explored if CAFF influences the nAChR conformational state using the AChR conformational-sensitive probe crystal violet (CrV) and AChR-rich membranes from T. californica. CAFF induced changes in the KD value of CrV in a concentra tion-dependent manner taking the nAChR to a state close to the desensitized one. In the presence of α-bungarotoxin, a specific nA ChR competitive antagonist, high concentrations of CAFF increased the KD value of CrV, compatible with a competition for the CrV site in the channel pore. The same effect was seen with galantamine, an AChE inhibitor and partial agonist of nAChR. To understand the molecular mechanism underlying the conformational changes of the nAChR, we expressed adult muscle or neuronal a7 nAChRs in BOSC cells, and performed single channel recordings with different CAFF concentrations in the presence or absence of ACh. At low concentrations (1-300 µM), CAFF activated muscle and a7 nAChRs, and the activation profile was independent of CAFF concentration. On the other hand, at high CAFF concentrations (up to 20 mM), the mean open duration decreased, the relative area of the briefer closed component and the cluster duration increased, and a flick ering behavior was observed, these suggesting that CAFF acts as an open channel blocker. Thus, we here demonstrate a dual effect of CAFF on muscle and a7 nAChRs, behaving as a weak agonist at low concentrations and as a negative modulator at high concen trations. Our results bring new information about the mechanism of modulation of pharmacology targets for the design of new therapies for the intervention in neurological diseases.